PENERAPAN METODE DISCOVERY LEARNING BERBANTUAN MEDIA GAMBAR PADA PEMBELAJARAN DARING MENULIS TEKS PROSEDUR - enden putri kusumawaty; Ika Mustika; Alfa Mitri Suhara (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
Learning to write procedural texts that is done online is still experiencing problems and problems in the results of students' writing procedural texts which are considered low. This is caused by the selection of learning methods and media that are not suitable for online learning. So that it makes students' understanding of the procedural text material still lacking. In applying online learning, it is the same as direct or face-to-face learning. Teachers are required to pay attention to the competencies to be taught. This is done so that learning remains effective and gets maximum results, especially in learning to write, for that researchers are interested in conducting research on the application of discovery learning methods assisted by image media in online learning to write procedural texts using qualitative descriptive methods. The sample for this study was 25 students of class VII-B SMP Al Falah Dago. Determining the results of the study using instruments in the form of student questionnaire sheets and test question sheets in the form of multiple choice questions and essay questions. The results of the study based on the student questionnaire instrument, showed a response of 70.10% of students assessing the discovery learning method was very good. The test results also show an average above the KKM with a score of 71.3 with a student's level of completeness as much as 70% in the good category. Based on these two results, it is concluded that the use of discovery learning methods assisted by image media has been successfully applied.